Visual dynamics: a WEB application for molecular dynamics simulation using GROMACS - Vieira, Ivo Henrique Provensi; Botelho, Eduardo Buganemi; de Souza Gomes, Thales Junior; Kist, Roger; Caceres, Rafael Andrade; Zanchi, Fernando Berton (BMC bioinformatics, 2023)
Background The molecular dynamics is an approach to obtain kinetic and thermodynamic characteristics of biomolecular structures. The molecular dynamics simulation softwares are very useful, however, most of them are used in command line form and continue with the same common implementation difficulties that plague researchers who are not computer specialists. Results Here, we have developed the VisualDynamics—a WEB tool developed to automate biological simulations performed in Gromacs using a graphical interface to make molecular dynamics simulation user-friendly task. In this new application the researcher can submit a simulation of the protein in the free form or complexed with a ligand. Can also download the graphics analysis and log files at the end of the simulation. Conclusions VisualDynamics is a tool that will accelerate implementations and learning in the area of molecular dynamics simulation. Freely available at https://visualdynamics.fiocruz.br/login , is supported by all major web browsers. VisualDynamics was developed with Flask, which is a Python-based free and open-source framework for web development. The code is freely available for download at GitHub https://github.com/LABIOQUIM/visualdynamics .